The Impact of Long-Term Relationships, Information Sharing, Agile, and Supply Chain Collaboration Towards Performance on Culinary Sectors - J.E. Sutanto; Christina Whidya Utami (International Journal of Supply Chain Management, 2021)
The development of the Indonesian economy cannot be separated from the role of micro, small, and medium enterprises (MSMEs) in various regions spread across Indonesia. Each city or district is a potential and developing area when viewed from the MSME business unit supported by the tourism industry in each of these areas. The MSMEs business unit in the culinary field faces many challenges such as increasingly tight competition, difficulty in obtaining funding or capital, inadequate marketing, lack of superior resources in the culinary field, lack of access to suppliers, and the emergence of new competitors. This problem relates to supply chain activities. The purpose of this study was to determine the effect of long-term relationships, information sharing, agile, supply chain capabilities, and supply chain applications on supply chain performance. This study used a sample of 150 respondents who had filled in the research instrument form, where the data collected were analyzed using SmartPLS.The results of this study indicate that all independent variables in this study have a positive and significant effect on the dependent variable, namely supply chain performance in the culinary sector in Indonesia. The Novelty, of the concept of this research is that the agile variable in previous studies is the dependent variable, but in this study the agile variable becomes the independent variable.